A P-Selectin/CD62P Monoclonal Antibody (LYP-20), in Tandem with Flow Cytometry, Detects in vivo Activated Circulating Rat Platelets in Severe Vascular Trauma - Chignier, Elza; Parise, Maud; McGregor, Lilian; Delabre, Caroline; Faucompret, Sylvie; McGregor, John (Thrombosis and Haemostasis, 1994)
P-selectin, also known as CD62P, GMP140 or PADGEM, is present in platelet a-granules and endothelial cell Weibel-Palade bodies and is very rapidly expressed on the surface of these cells on activation. In this study, an anti P-selectin monoclonal antibody (LYP20) was used, in tandem with flow cytometry, to identify activated platelets at the site of induced vascular trauma or in peripheral blood. Moreover, electron microscopy was performed to characterize sites of vascular trauma and quantify the number of adhering platelets. The same induced vascular trauma was observed to result into animals responding in 2 different ways (Group I, Group II) following the degree of platelet activation. Five rats, out of 14 with induced vascular trauma, had more than half of their circulating platelets expressing P-selectin when drawn at the site of the trauma (67.4% ± 3.44) or in peripheral blood (78.5% ± 2.5) (Group I). In the remaining 9 animals a much smaller proportion of circulating platelets expressed P-selectin when assayed from trauma sites (18% ± 3.34) or in peripheral blood (18.0% ± 4.30) (Group II). Enhanced P-selectin expression by circulating platelets in Group I, compared to Group II, appears to be linked to the degree of activated platelets adhering at sites of trauma (171 ± 15 × 103 platelets versus 48 ± 31 × 103 platelets per mm2). In the 5 control animals, that were not operated on, platelets expressing P-selectin when drawn at the site of a mock trauma (7.0% ± 1.84) or in the peripheral blood (11.2% ± 3.30) showed little activation. In addition, no platelet adhesion was seen on the vascular bed of these animals. Results from this study show that analysis of P-selectin (CD62P) expression, in circulating platelets, is a valuable and rapid marker of platelet activation following severe vascular trauma induced in rats. However, activated platelets were not detected to the same extent in the peripheral blood of all animals having undergone vascular trauma. It is conceivable that platelets, depending on the degree of activation, may be actively sequestered in organs and prevented from circulating. Alternatively, P-selectin may be rapidly endocytosed, or not expressed, by activated circulating platelets depending on the type of agonists implicated in vivo activation.